Distribusi zakat di Indonesia: antara sentralisasi dan desentralisasi - Aden Rosadi; Mohamad Anton Athoillah (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2015)
The problem of poverty that be falls in the muslim communities is influenced by the systems used inthe distribution of zakah funds. Each system used has some advantages and disadvantages in accordancewith the priority issues to be resolved. If the priority is to reduce poverty, then decentralization isthe best choice of either of these options. This paper would like to reiterate the importance of decentralizeddistribution of charity funds so that funds raised by an area will be returned to the area and theproblems of poverty faced from which the funds collected will soon be resolved.